Tinjauan Yuridis Kelalaian Pengemudi Pemadam Kebakaran terhadap Kecelakaan Lalu Lintas yang Menyebabkan Hilangnya Nyawa: Legal Review of Firefighter Driver Negligence in Traffic Accidents Resulting in Loss of Life - Mukson Sayuti Raka Dewi; Muhammad Aenur Rosyid (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2023)
Accidents caused by firefighter drivers for their negligence and resulting in the loss of other people's lives are certainly cases of accidents that can create legal dualism in the application of criminal responsibility to firefighter drivers. The aims of this research are: 1). To find out about positive legal reviews of the form of criminal responsibility for firefighter drivers for their negligence resulting in accidents and deaths of other road users; 2). To find out the review of Islamic criminal law on the criminal responsibility of firefighter drivers for their negligence resulting in accidents and loss of lives of other motorists. This research is based on extracting secondary data classified into primary, secondary and tertiary legal materials using descriptive data analysis techniques and data validity through source triangulation. In this study, researchers concluded 2 things, namely: 1). Fire truck drivers who cause traffic accidents and the death of other road users based on their negligence can be subject to Article 359 of the Criminal Code Jo. Article 310 paragraph 4 of Law Number 22 of 2009 concerning Road Traffic and Transportation for his actions; 2). The act of taking someone's life in the case of a fire truck accident based on negligence according to Islamic law is classified as wrongful killing and is subject to criminal sanctions in the form of payment of a diyat of 100 camels and ta'zir determined by the local authorities Kecelakaan yang disebabkan oleh pengemudi pemadam kebakaran atas kelalaiannya serta mengakibatkan hilangnya nyawa orang lain tentu menjadi kasus kecelakaan yang dapat membuat dualisme hukum dalam penerapan pertanggungjawaban pidana terhadap pengemudi pemadam kebakaran, Tujuan penelitian ini adalah : 1). Untuk Mengetahui mengetahui tinjauan hukum positif terhadap bentuk pertanggung jawaban pidana pengemudi pemadam kebakaran atas kelalaiannya sehingga mengakibatkan kecelakaan dan meninggalnya pengguna jalan lain; 2). Untuk mengetahui tinjauan hukum pidana islam terhadap pertanggung jawaban pidana pengemudi pemadam kebakaran atas kelalaiannya sehingga mengakibatkan kecelakaan dan hilangnya nyawa pengendara lain. Penelitian ini didasarkan pada penggalian terhadap data sekunder yang diklasifikan dalam bahan hukum primer, sekunder dan tersier dengan tekhnik analisis data deskriptif dan keabsahan data melalui triangulasi sumber. Dalam penelitian ini, peneliti menyimpulkan2 hal, yaitu: 1). Pengemudi truk pemadam kebakaran yang menyebabkan kecelakaan lalu lintas dan meninggalnya pemakai jalan lain berdasarkan kelalainnya dapat dikenakan Pasal 359 KUHP Jo. Pasal 310 ayat 4 Undang-undang Nomor 22 Tahun 2009 tentang Lalu Lintas dan Angkutan Jalan atas tindakannya; 2). Tindakan menghilangkan nyawa seseorang dalam kasus kecelakaan truk pemadam kebakaran berdasarkan kelalaiannya menurut hukum islam digolongkan pada pembunuhan tersalah dan dikenakan sanksi pidana berupa pembayaran diyat 100 ekor unta dan ta’zir yang ditentukan oleh penguasa setempat